Evaluation of Kidneys’ Functional State in Acute Lymphoblastic Leukemia Patients Following Hematopoietic Stem Cell Transplantation - Murzakhmetova, Aigerim; Kemaykin, Vadim; Kuttymuratov, Aset; Ainabay, Ayagul; Meiramova, Assel; Tursynbet, Yernar; Ainabekova, Bayan (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Hematopoietic Stem Cell Transplantation (HSCT) has recently been a widely used method of therapy in various fields of current medicine, particularly in hematology.Some patients develop renal disorders following HSCT. AIM: This study aims to evaluate the dynamics of changes in the functional state of the kidneys in patients with ALL after HSCT. METHODS: In the period from 2015 to 2021, for the first time in Kazakhstan, patients with acute lymphoblastic leukemia (ALL) who underwent allogeneic and haploidentical HSCT were prospectively examined. RESULTS: We determined that the greatest decrease in glomerular filtration rate occurred in the group of patients who underwent haploidentical bone marrow transplantation. Moreover, we believe that our results are related to known contributing risk factors, such as the type of performed transplantation and the duration of taking medications for the prevention of graft versus host disease. Our results also indicate that the lethal outcome in the group with haploidentical HSCT in the studied patients with ALL was greater than in the group with allogeneic HSCT. CONCLUSION: In conclusion, a decrease in kidney function in patients who have survived HSCT is probably a common complication; however, further prospective studies are required to confirm these results to develop additional algorithms for the treatment and prevention of renal disorders in patients with acute leukemia after HSCT.